Incidences and reporting rates of incidental findings on lumbar, thoracic, and cervical spinal magnetic resonance images and extra-neuronal findings on brain magnetic resonance imagesö - Kızılgöz, Volkan; Aydın, Hasan; Sivrioğlu, Ali Kemal; Özcan, Ümit Can; Menderes, Utku; Karayol, Sunay Sibel; Erdem, Ahmet (The European Research Journal, 2019)
Objective: This study aimed to evaluate the incidence rates, reporting rates, and the best imaging plane and sequence for incidental findings in patients undergoing spinal and brain magnetic resonance (MR) imaging.Methods: Three experienced radiologists retrospectively re-evaluated the MR images of 1056 consecutive patients.Results: The incidence rates for extraspinal incidental findings for the images of the lumbar, thoracic, and cervical spine, and extra-neuronal incidental findings on MR images of the brain were 35.47%, 32.25%, 29.16%, and 54.35%; respectively, with reporting rates of incidental findings for these examinations of 31.47%, 8.33%, 29.50%, and 59.62%; respectively. For all examination types, the T2-weighted sequence and the axial plain were the best to reveal the incidental findings of MR examinations, other than that of the cervical spine. Conclusions: Incidental findings, which are commonly detected during routine spinal and brain MR evaluations, are occasionally omitted from formal radiological reports in daily practice. We strongly recommend checking the T2-weighted axial plane for MR imaging of the lumbar, thoracic spine and brain and taking a second look at the T2-weighted sagittal plane MR images of the cervical spine during radiological evaluations.